1979
DOI: 10.1111/j.1399-3054.1979.tb02616.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonally Induced Polyembryos in Wheat

Abstract: It had been shown previously that wheat plants, which had been sprayed with auxin herbicide al flowering lime, produced seeds with extra shoots. These shoots have now been found lo belong So new, and relatively normal, embryos formed in the lower part of the scutellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…We observed multiple (two to four) roots in the polyembryoids very rarely. Usually, they were fused (fasciated) to each other, which was also reported by other authors (Ferguson et al, 1979) supposing that polymeric structures with a common root pole should not be qualified as cleavage polyembryony. According to Fischer et al (1997), the phenomenon should be taken as a partial multiplication of embryonic axes in contrast to their full multiplication (polyembryony).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We observed multiple (two to four) roots in the polyembryoids very rarely. Usually, they were fused (fasciated) to each other, which was also reported by other authors (Ferguson et al, 1979) supposing that polymeric structures with a common root pole should not be qualified as cleavage polyembryony. According to Fischer et al (1997), the phenomenon should be taken as a partial multiplication of embryonic axes in contrast to their full multiplication (polyembryony).…”
Section: Discussionsupporting
confidence: 66%
“…Some workers consider them as manifestations of a cleavage polyembryony (Haccius, 1955;Vidovencova, 1992, 1994). Other authors argue against the term "cleavage embryos" for these structures, since their components are not fully autonomic (Ferguson et al, 1979). The polymeric complexes were even ascribed to vegetative polyembryony-peculiar plant "pedogenesis" (child reproduction), which partenogenetically appears in response to growth substances (Yakovlev and Snegirev, 1954).…”
Section: Developmental Biology Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferguson et al (1979) observed that wheat plants produced polyembryos when sprayed right after flowering with a herbicide containing 2,4-D. The extra embryos formed in the lower part of the scutellum.…”
Section: Discussionmentioning
confidence: 99%
“…Ferguson et al (1979) observed that wheat plants produced polyembryos when sprayed immediately after flowering with a herbicide containing 2,4-D. Erdelska and Vidovencova (1992) described the suspensorial embryo and cleavage of the zygotic Genetic characterization of cleavage polyembryos in rice X-c Yang and C-m Hwa proembryo in maize. Cleavage of the zygotic proembryo could also be induced by a 2,4-D treatment.…”
Section: Discussionmentioning
confidence: 99%